Cardiac Autonomic Dysfunction in the Early Phase after Left Ventricular Assist Device Implant: Implications for Surgery and Follow-Up?. Issue 6 (June 2013) - Compostella, Leonida; Russo, Nicola; Setzu, Tiziana; Tursi, Vincenzo; Bottio, Tomaso; Tarzia, Vincenzo; Compostella, Caterina; Covolo, Elisa; Livi, Ugolino; Gerosa, Gino; Sani, Guido; Bellotto, Fabio
Purpose: In congestive heart failure (CHF) patients, a profound cardiac autonomic derangement, clinically expressed by reduced heart rate variability (HRV), is present and is related to the degree of ventricular dysfunction. Implantation of a left ventricular assist device (LVAD) can progressively improve HRV, associated with an increased circulatory output. Data from patients studied at different times after LVAD implantation are controversial. The aims of this study were to assess cardiac autonomic function in the early phases after axial-flow LVAD implantation, and to estimate the potential relevance of recent major surgical stress on the autonomic balance. Methods: HRV (time-domain; 24-h Holter) was evaluated in 14 patients, 44.8 ± 25.8 days after beginning of Jarvik-2000 LVAD support; 47 advanced stage CHF, 24 cardiac surgery (CS) patients and 30 healthy subjects served as control groups. Inclusion criteria: sinus rhythm, stable clinical conditions, no diabetes or other known causes of HRV alteration. Results: HRV was considerably reduced in LVAD patients in the early phases after device implantation in comparison to all control groups. A downgrading of HRV parameters was also present in CS controls. Circadian oscillations were highly depressed in LVAD and CHF patients, and slightly reduced in CS patients. Conclusions: In CHF patients supported by a continuous-flow LVAD, a profound cardiac dysautonomia is still evident in the first two months from the beginning of circulatory support; the degree of cardiac autonomic imbalance is even greater in comparison to advanced CHF patients. The recent surgical stress could be partly linked to these abnormalities.